1978
DOI: 10.1901/jeab.1978.29-419
|View full text |Cite
|
Sign up to set email alerts
|

TIME ALLOCATION IN CONCURRENT SCHEDULES: THE EFFECT OF SIGNALLED REINFORCEMENT1

Abstract: The responses of five pigeons were reinforced on concurrent variable-interval variableinterval reinforcement schedules in which changeover key responses changed the stimulus and reinforcement schedules associated with the food key. While the reinforcement availability in one component remained unchanged throughout the experiment, the reinforcement availability in the other component was, during several conditions, signalled by the onset of an additional discriminative stimulus. During unsignalled conditions, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
22
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 16 publications
4
22
0
Order By: Relevance
“…Results showed that when reinforcement availability was signaled, both responding and time allocation to the signaled schedule were decreased. As in the study of Marcucella and Margolius (1978), the decrease in responding was markedly greater than the decrease in time allocation.…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…Results showed that when reinforcement availability was signaled, both responding and time allocation to the signaled schedule were decreased. As in the study of Marcucella and Margolius (1978), the decrease in responding was markedly greater than the decrease in time allocation.…”
Section: Resultsmentioning
confidence: 72%
“…Results showed that when reinforcement availability was signaled, both responding and time allocation to the signaled schedule were decreased. As in the study of Marcucella and Margolius (1978), the decrease in responding was markedly greater than the decrease in time allocation.These studies show that the basic effect of signaling reinforcement on one alternative in a concurrent schedule is a decrease in responding on the signaled alternative. This produces a concomitant change in relative behavior and time allocation that is markedly greater for behavior than for time.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…First, the synthetic concurrent procedure, from MacDonall's Experiment 1, required rats to make two presses on the changeover lever to change the stimuli and associated schedules, which resembles FR 2 for switching. Marcucella and Margolius (1978) and Pliskoff and Fetterman (1981) used concurrent VI procedures with main and switching keys and pigeons as subjects, and also required completing an FR changeover requirement to change the stimuli and associated schedules. To prevent responding during the FR changeover requirement, Marcucella and Margolius (1978) and Pliskoff and Fetterman (1981) stopped illuminating the main key until the FR was completed.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Hershiser and Trapold does not provide the necessary data to assess whether this switching pattern of responding occurred, but others have reported such as pattern when studying mixed vs. multiple schedules (e.g., Dinsmoor, Browne, Lawrence, & Wasserman, 1971). In addition, Marcucella and Margolius (1978) appeal to a similar pattern to account for responding under concurrent VI VI schedules. Obviously further assessment of commitment and noncommitment procedures are needed as they relate to studies of preference.…”
Section: Discussionmentioning
confidence: 99%